Internship report on budgetary policies, procedures and controls: South Asian Institute of Policy and Governance - Mim, Maisha Tanzeem (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.